Allergic rhinitis – a review of current diagnostic and therapeutic methods - Kacper Kwiliński; Maja Kucharska; Monika Szyszka; Barbara Wawrzyńska; Paulina Przybysz; Agata Paruch; Magdalena Wadowska (Quality in Sport, 2024)
Allergic rhinitis (AR) is a common disease characterized by inflammation of the nasal mucosa caused by exposure to allergens such as pollen, house dust mites, animal dander, and molds. Symptoms include sneezing, nasal itching, watery discharge, and nasal congestion, often associated with conjunctivitis. AR can significantly reduce patients' quality of life, affecting their ability to perform daily activities and causing sleep disturbances and fatigue.